Stocking density effect on survival and growth of early life stages of maraena whitefish, Coregonus maraena (Actinopterygii: Salmoniformes: Salmonidae) - Vlastimil Stejskal; Jan Matousek; Roman Sebesta; Joanna Nowosad; Mateusz Sikora; Dariusz Kucharczyk (Acta Ichthyologica et Piscatoria, 2021)
The maraena whitefish, Coregonus maraena (Bloch, 1779), is often considered a suitable candidate for intensive aquaculture diversification in the EU. However, only a few such farms in Europe are in operation. Rearing this species in recirculating aquaculture systems is a recent innovation, and optimisation is necessary to standardise aspects of larviculture. This 30-day study investigated the effect of stocking densities of 25/L, 50/L, 100/L, and 200/L on the survival and growth of maraena whitefish larvae in a recirculating aquaculture system. The four groups of larvae (initial weight = 7.4 ± 0.1 mg; initial total length = 13.0 ± 0.1 mm) in three repetitions were reared in a recirculating system. Larvae were fed fresh live brine shrimp metanauplii every 3 h at a rate converted to larval stocking density. After the experiment, 10 larvae from each tank (30 of each density group) were weighed on a digital microbalance (ABJ 220-4M KERN, Germany, readout = 0.1 mg) and measured manually on images taken with Leica MZ16 A stereomicroscope and a digital colour camera with 5-megapixel resolution for Leica DFC420 Image Analysis. No significant differences in final body weight, total length, size heterogeneity, condition factor, or survival were found among treatments (P > 0.05). The highest non-significant survival rate and growth parameters were observed in larvae reared at 25/L. On the contrary, it is possible to rear maraena whitefish larvae at high stocking density without any subsequent negative consequences for growth and survival. As no significant differences in any evaluated parameter were observed between groups of larvae at the highest and lowest stocking density, we conclude that it is possible to rear maraena whitefish larvae at high stocking density (and 200/L) without any subsequent negative consequences for growth and survival.